Determination of the Predictive Value of Serum Bilirubin in Patients with Ischemic Stroke: A Prospective Descriptive Analytical Study - Elnaz Sagheb Asl; Aliakbar Taheraghdam; Farzad Rahmani; Reza Javadrashid; Samad Eslam Jamal Golzari; Neda Ghaemian; Yalda Sadeghpour; Robab Mehdizadeh Esfanjani; Hassan Soleimanpour (Tabriz University of Medical Sciences, 2018)
Purpose: In all types of ischemic stroke, especially in the acute phase, excessive oxidative stress causes structural and functional damage to the brain. This may play a major role in the pathophysiology of the brain damage. Higher serum levels of bilirubin have therapeutic effects in oxidative stress-induced stroke. Nevertheless, role of increased serum levels of bilirubin in the acute phase of ischemic stroke is controversial. Methods: This study was a cross-sectional prospective descriptive study conducted in the Emergency Department (ED) of Imam Reza hospital, Tabriz University of Medical Sciences, Tabriz, Iran, throughout six months. 275 ischemic stroke patients were evaluated based on their brain CT scan infarct size, NIHSS, MRS, and serum levels of bilirubin. Later, data were analyzed using SPSS software. Results: Total, direct and indirect bilirubin levels were significantly higher in expired patients (p< 0.0001). Total (p< 0.0001), direct (p< 0.0001) and indirect (p< 0.0001) bilirubin levels, NIHSS score (p< 0.0001), and ischemic area (p< 0.0001) significantly predicted the outcome in these patients. Conclusion: Total, direct and indirect bilirubin levels was significantly associated with mortality in the acute phase of ischemic stroke patients.